PENGARUH UKURAN PERUSAHAAN, FINANCIAL LEVERAGE, STRUKTUR KEPEMILIKAN, CASH HOLDING, REPUTASI AUDITOR TERHADAP INCOME SMOOTHING (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR TERDAFTAR DI BEI PERIODE 2018 - 2020) - Endang Purwaningsih; Oktofiana Busa Taran Wanan (STIE St. Pignatelli Surakarta, 2022)
This study aims to determine the effect ofcompany size, financial leverage,ownership structure, cash holdings,auditor's reputation for income smoothingin manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique used secondary data sources, namely data obtained or collected by researchers from various existing sources. The population used in this study were 193 manufacturing companies with a total sample of 40 companies. The analytical method used is the classical assumption test and multiple regression test.Based on the analysis conducted, it can be concluded that this study meets the requirements of the classical assumption test. Hypothesis testing using t test shows that firm size has a significant positive effect on income smoothing with a sig value of 2.6%, financial leverage has a significant negative effect on income smoothing with a sig value of 3.0%, managerial ownership has a significantpositive effect on income smoothing with a sig value of 1.3 %, institutional ownership has a significant negative effect on income smoothing with a sig value of 1.8%, cash holding a significantly negative effect on income smoothing with a sig value of 3.8%, and auditor reputation has a significant positive effect on income smoothing with a sig value of 4.6%.The results of the f test together with independent variables including company size, financial leverage, managerial ownership, institutional ownership, cash holding and auditor reputation have a significant effect on income smoothing. The value of the coefficient of determination (Adjusted R2) from the equation tested in this study was 42.8%. This indicates that income smoothing is only explained by 42.8% by company size, financial leverage, managerial ownership, institutional ownership, cash holding and auditor reputation while the rest is explained by other variables outside the equation.